Functional characterization of novel variants in SMPD1 in Indian patients with acid sphingomyelinase deficiency. Issue 10 (3rd August 2021) - Deshpande, Dipti; Gupta, Shailesh Kumar; Sarma, Asodu Sandeep; Ranganath, Prajnya; Jain S., Jamal Md Nurul; Sheth, Jayesh; Mistri, Mehul; Gupta, Neerja; Kabra, Madhulika; Phadke, Shubha R.; Girisha, Katta M.; Dua Puri, Ratna; et al.
Abstract: Pathogenic variations in SMPD1 lead to acid sphingomyelinase deficiency (ASMD), that is, Niemann‐Pick disease (NPD) type A and B (NPA, NPB), which is a recessive lysosomal storage disease. The knowledge of variant spectrum in Indian patients is crucial for early and accurate NPD diagnosis and genetic counseling of families. In this study, we recruited 40 unrelated pediatric patients manifesting symptoms of ASMD and subnormal ASM enzyme activity. Variations in SMPD1 were studied using Sanger sequencing for all exons, followed by interpretation of variants based on American College of Medical Genetics and Genomics & Association for Molecular Pathology (ACMG/AMP) criteria. We identified 18 previously unreported variants and 21 known variants, including missense, nonsense, deletions, duplications, and splice site variations with disease‐causing potential. Eight missense variants were functionally characterized using in silico molecular dynamic simulation and in vitro transient transfection in HEK293T cells, followed by ASM enzyme assay, immunoblot, and immunofluorescence studies. All the variants showed reduced ASM activity in transfected cells confirming their disease‐causing potential. The study provides data for efficient prenatal diagnosis and genetic counseling of families with NPD type A and B. Abstract : We describe the clinical features and SMPD1 variant spectrum in Indian patients affected with Nieman–Pick disease type A and type B. We functionally characterized the variants using in silico molecular dynamic simulation and in vitro methods like ASM enzyme assay, immunoblotting, and immunofluorescence to understand the pathogenic nature of the variants.